Antioxidant Activity Test of Ketapang Leaf Extract (Terminalia catappa L.) Using the B-Carotene Bleaching Method - Wati, Vega (UNIVERSITAS MUSLIM INDONESIA, 2024)
Ketapang (Terminalia catappa L.) is a plant that belongs to the Combretaceae family which is spread in tropical countries, including Indonesia. Ketapang leaves (Terminalia catappa L.) contains flavonoid compounds which function as antioxidants. The purpose of this study was to determine the antioxidant activity of ketapang leaf extract (Terminalia catappa L.) using the β-carotene bleaching method. The extract was obtained through the maceration method, then the yield percentage was 20.25%. Phytochemical screening test was carried out identifiy chemical compounds and obtained namely alkaloids, flavanoids, tannins, saponins, and steroids. Antioxidant activity was performed using UV-Vis spectrophotometry with a wavelength of 538 nm. The results showed that the antioxidant activity of ketapang leaf extract (Terminalia catappa L.) of 56.5% was an intermediate antioxidant (moderate), then in a standard solution of quercetin has a strong antioxidant activity of 72.3%. Keywords : Ketapang leaves (Terminalia catappa L.), Screening Phytochemicals, Antioxidants, B-carotene bleaching, Spectrophotometry UV-Vis.